PENGARUH CORPORATE GOVERNANCE DAN KOMPENSASI EKSEKUTIF TERHADAP TAX AVOIDANCE - Suri Mahrani (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2025)
The purpose of this study is to determine and analyze the effect of corporate governance and executive compensation on tax avoidance. Corporate governance is proxied by institutional ownership, the board of commissioners, the audit committee, and audit quality. The population of this study was 86 mining companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Sampling used purposive sampling, with 16 companies selected. The data analysis technique used was multiple linear regression. The results of this study indicate that the board of commissioners and the audit committee have an influence on tax avoidance.